1999
DOI: 10.1107/s0909049598017919
|View full text |Cite
|
Sign up to set email alerts
|

XANES study of the support effect on the state of platinum catalysts

Abstract: Pt I~u and Ln-edges XANES clarified the oxidation state of platinum catalysts supported on various metal oxides. The acidbase property seemed one of the most dominant factors to control the electron state of platinum. On the reduced samples, there was a tendency that acidic support reduced the 5d-electron density of platinum, while the oxidized samples on acidic support contained more metallic platinum. The latter tendency agreed well with high activity of platinum catalysts on acidic supports toward propane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…In the previous paper, the authors reported that the white line intensity at Pt L III -edge XANES spectra of platinum catalysts supported on various oxides decreases with an increase in the acid strength of support materials (Yoshida et al, 1999;Yazawa et al, 2000). The present study revealed that the additives have the same effect.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the previous paper, the authors reported that the white line intensity at Pt L III -edge XANES spectra of platinum catalysts supported on various oxides decreases with an increase in the acid strength of support materials (Yoshida et al, 1999;Yazawa et al, 2000). The present study revealed that the additives have the same effect.…”
Section: Resultssupporting
confidence: 70%
“…In this atmosphere, noble metal is oxidized to some extent under the reaction condition, and the oxidation state of noble metal is one of key factors to control its performance. Recently, in propane combustion over noble metal catalysts, the authors showed that the catalytic activity can be improved by the selection of support materials through the controlling the oxidation state of noble metal (Yazawa et al, 1999;Yoshida et al, 1999;Yazawa et al, 2000). In the case of platinum catalysts, the stronger acidic support gives the higher oxidationresistance to platinum catalyst, leading to the higher catalytic activity for propane combustion, since combustion activity of platinum decreases as platinum is oxidized (Voelter et al, 1987;Nunan et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…2 a, e ). The white line intensity directly reflects the unoccupied density of states of Pt 5d orbitals 37 . The lower intensity of white line peak for Pt/S–C suggests that the S–C support can donate electrons to Pt nanoclusters, which leads to an electron-enriched state of Pt nanoclusters on S–C.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic deactivation of platinum catalysts by O 2 and NO 2 due to oxides formation in the reaction has been proved and investigated in details [9][10][11][12]. In the research of support effect on the state of platinum catalysts, Yoshida et al [15] suggested that electrophilic acidic support suppress the formation of platinum oxides through electrons donation from support to platinum. The electron-interaction between platinum and support may be considered as promising tool to suppress the formation of platinum oxides.…”
Section: Introductionmentioning
confidence: 99%